3D formulation for revolute clearance joints - Marques, Pedro Filipe Lima (2017)
In this work, a general and comprehensive methodology for the modeling and analysis of spatial multibody systems with revolute clearance joints is presented. The proposed formulation considers the journal and the bearing elements as two cylindrical colliding bodies. All the potential contact scenarios and their kinematics are determined from the relative positions of two cylinders and from the kinematics of the multibody systems. It must be highlighted that both radial and axial clearances are modeled under the new proposed approach. The methodology presented here is demonstrated by using a spatial slider-crank mechanism that incorporates a spatial revolute clearance joint. The results show that the system’s response is considerably influenced by the existence of a clearance joint.